Differences in Providing Health Education between Flip Sheet Media and Video Media on Interest in Using IUDs among Pregnant Women in the Third Trimester at the Samboja Community Health Center in 2023 - Ra'idah Nabilah (Formosa Journal of Science and Technology, 2023)
The Samboja Health Center located in Kutai Kartanegara Regency is known to have IUD users in 2020 there were 119 people (4.2%) out of 2,859 PUS and in 2021 there were 263 people (8.7%) out of 3,022 PUS.  This type of research is quasi-experimental with the research design using a non-aquavalent pre- and post-test control group. The sampling technique was total sampling so that the sample totaled 30 people, divided into intervention and control groups of 15 people each. Sampling technique using purposive sampling. Data analysis using paired sample t test. The interest in using the IUD after providing health education with video media was all interested in using the IUD (100%), while the flipchart media for trimester III pregnant women was mostly interested in using the IUD (80%). There are differences in the provision of health education between flipchart media and video media on interest in using IUDs in trimester III pregnant women at the Samboja Health Center (p value: 0.001). There are differences in the provision of health education between flipchart media and video media on interest in using IUDs in trimester III pregnant women.